INDUSTRY 4.0 AND SMART CITIES MOBILITY - Alessandro Aveni (Revista Processus de Políticas Públicas e Desenvolvimento Social, 2020)
The paper resumes an exploration research developed in Brazil during a four year research activity, having focus on metropolitan and smart cities mobility showing the case of Brasilia Metropolitan Area. The research uses two techniques: bibliographic and filed research for primary data. The approach was qualitative and moderate quantitative from secondary data. Quantitative figures were based on indicators from consulting firm research reports. Indicators are based on three steps: evidence of planning, evidence of system and evidence of market. The period of research was august 2018 – November 2018.  Main results of the research are: in Brasilia no electric mobility planning was found form institutional evidences to develop the Smart City initiative integrated to Industry 4.0. In spite of lack of public planning, there is a great opportunity for business. The main metropolitan area is worth some 3 million inhabitants, almost 7 including surrounding metropolitan areas with millions vehicles Threats are no fiscal incentives and infrastructure of electric posts able to sustain car supply and no offer of electric/hybrid cars and conversion kits. In the other hand there is a great number of cars and increasing urban mobility, a great number of public and private vehicles and the urban transportation of goods uses motorcycles, van, light trucks with increasing operational cost mainly due to gasoline costs.